2022-RA-1137-ESGO Use of an allogeneic, cell-based vaccine DCP-001 in high grade Serous Ovarian cancerpatients after primary treatment; A phase I clinical trial. (20th October 2022) - Vledder, Annegé; van Zeeburg, Hester; Pas, Rob ten; Eerkens, Anje; Brummel, Koen; Wang Yin, Kiave Ho; Tabruyn, Sebastien; Singh, Satwinder Kaur; de Bruyn, Marco; Rovers, Jeroen; Nijman, Hans Wilhelm
Abstract : Introduction/Background: DCP-001 is a cell-based relapse vaccine developed to prevent disease recurrence following primary treatment. Trials in patients with acute myeloid leukemia have shown DCP-001 to be well-tolerated and interim results of an ongoing phase II study (ADVANCE II) revealed durable clinical responses. Interestingly, the tumor-associated antigens expressed by DCP-001 are shared across tumor types, most notably ovarian cancer (OC). Here, we present data on the anti-tumor efficacy of DCP-001 in humanized OC mice models and initial safety and tolerability data of the phase I clinical trial evaluating DCP-001 immunization in high-grade serous OC patients. Methodology: Prior to initiation of a clinical trial, the efficacy of DCP-001 against OC cells was tested in a mouse model. Humanized mice were engrafted with SKOV3 cells and vaccinated when tumors reached an average volume of 75–100 mm 3 . Impact of DCP-001 vaccination was assessed on tumor growth. In the phase I trial, patients receive 6 immunizations with DCP-001; 4 bi-weekly vaccinations containing 25x10 6 cells followed by 2 monthly boosters containing 10x10 6 cells. Safety and tolerability is monitored up to 28 days after the last vaccination. Results: In a pre-clinical humanized OC mouse model, DCP-001 vaccination led to significant reduction of tumor growth rate resulting in partial and complete tumor regressions. In patients, DCP-001 vaccination was well-tolerated and DCP-001 related adverse events were only mild to moderate and mostly related to local injection site reactions. Patients reported fatigue, diarrhea, headache, nausea, temperature elevation and generalized joint and muscle pain. No severe adverse events were observed. Conclusion: Pre-clinical data in humanized OC mice demonstrated that DCP-001 reduces tumor growth and provided a rational for clinical therapeutic exploitation in OC patients. Initial data from the phase I trial demonstrates that DCP-001 is safe and well-tolerated and justifies continued exploration of this novel immunotherapy concept in OC patients.